2022
DOI: 10.1007/s41982-022-00111-1
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Hominin Activities in the Zooarchaeological Assemblage of Barranco León (Orce, Granada, Spain)

Abstract: Little is known about the subsistence practices of the first European settlers, mainly due to the shortage of archaeological sites in Europe older than a million years. This article contributes to the knowledge of the subsistence of the first Europeans with new zooarchaeology and taphonomic data from the Palaeolithic site of Barranco León (Orce, Granada, Spain). We present the results of the analysis of the faunal assemblages retrieved in the context of new excavations undertaken between 2016 and 2020. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 69 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…Of this scarce evidence, only one reference is outside the Iberian Peninsula, in the Greek locality of Marathousa [58]. In particular, a limited number of cut marks identified on specimens from the sites of Barranco León [59] and Fuente Nueva-3 [20] allow us to propose human access to hippopotamus carcasses in the Early Pleistocene. More evident seems to be the accumulation of hippopotamus remains in the locality of Bolomor Cave at the end of the Middle Pleistocene [22].…”
Section: Paleoecological Considerationsmentioning
confidence: 99%
“…Of this scarce evidence, only one reference is outside the Iberian Peninsula, in the Greek locality of Marathousa [58]. In particular, a limited number of cut marks identified on specimens from the sites of Barranco León [59] and Fuente Nueva-3 [20] allow us to propose human access to hippopotamus carcasses in the Early Pleistocene. More evident seems to be the accumulation of hippopotamus remains in the locality of Bolomor Cave at the end of the Middle Pleistocene [22].…”
Section: Paleoecological Considerationsmentioning
confidence: 99%
“…The Orce sub-basin preserves a unique fossil record of terrestrial vertebrates, including two archaeological sites dated to ~ 1.4 Ma (see review in Palmqvist et al, 2016) that mark the earliest presence of hominins in Western Europe: Barranco León (BL) and Fuente Nueva-3 (FN3). BL and FN3 preserve huge assemblages of skeletal remains of large mammals and Oldowan tools, which are linked through the presence of anthropogenic cut and percussion marks, as well as a human deciduous tooth in the case of BL, which is at this moment the oldest hominin fossil found in Western Europe (Martínez-Navarro et al, 1997Oms et al, 2000aOms et al, , 2000bEspigares et al, 2013Espigares et al, , 2019Toro-Moyano et al, 2013;Titton et al, 2021;Yravedra et al, 2021Yravedra et al, , 2022Palmqvist et al, 2023). Moreover, the Venta Micena site (VM, 1.6-1.5 Ma), which is slightly older than BL/FN3 and has been interpreted as a denning area of the giant hyena Pachycrocuta brevirostris (Arribas and Palmqvist, 1998;Palmqvist and Arribas, 2001;Palmqvist et al, 2022b), provides an excellent record of the large mammal community that preceded the hominin dispersal in the basin (Martínez-Navarro, 1991;Mendoza et al, 2005;Rodríguez-Gómez et al, 2017).…”
Section: Geological and Paleontological Settingmentioning
confidence: 99%
“…In particular, the ∼1.2 Ma open-air site of Fuente Nueva 3 (FN3; see Supplementary Materials) has been used to defend the scenario of direct competition between both P. brevirostris and early European populations of Homo for the consumption of large mammal carrion (Espigares et al, 2013(Espigares et al, , 2019Yravedra et al, 2024). Current evidence supporting P. brevirostris activity at this site includes a high prevalence of bones displaying carnivore induced damage in association with abundant P. brevirostris coprolites (Espigares et al, 2023(Espigares et al, , 2013, and the notably large size of the tooth marks observed on some of the bones.…”
Section: Introductionmentioning
confidence: 99%